2020
DOI: 10.1101/2020.12.17.423230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absence of electroencephalographic evidence of implicit action-effect intentional binding with varying effect probability

Abstract: The subjective experience of an attraction in time of an action and the event caused by the action is known as the intentional binding phenomenon. Intentional binding is a robust phenomenon and has been associated with subjective sense of agency. In this study we tested possible electrophysiological equivalents to the intentional binding phenomenon under a simple action-effect task, where pressing of a button caused tones to occur at different pitches or delays with different probabilities. Changing the probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Some have used EEG to measure intentional binding, an internal process that was identified as crucial for the normal experience of agency [116], [117]. However, the relationship between EEG and intentional binding is still controversial [118] and EEG recording has several drawbacks when integrated into avatar embodiment applications: on top of being time-consuming to set up, most non-intrusive EEG systems are very sensitive to muscle activity and electrical noise in the environment, limiting the embodiment to an immobile experience with very little possibilities of interaction. Further details on EEG setup and signal processing for the study of body ownership illusions can also be found in the article of Spanlang et al [87].…”
Section: Objective Measuresmentioning
confidence: 99%
“…Some have used EEG to measure intentional binding, an internal process that was identified as crucial for the normal experience of agency [116], [117]. However, the relationship between EEG and intentional binding is still controversial [118] and EEG recording has several drawbacks when integrated into avatar embodiment applications: on top of being time-consuming to set up, most non-intrusive EEG systems are very sensitive to muscle activity and electrical noise in the environment, limiting the embodiment to an immobile experience with very little possibilities of interaction. Further details on EEG setup and signal processing for the study of body ownership illusions can also be found in the article of Spanlang et al [87].…”
Section: Objective Measuresmentioning
confidence: 99%